2019
DOI: 10.3390/ijerph16203929
|View full text |Cite
|
Sign up to set email alerts
|

Land Subsidence in a Coal Mining Area Reduced Soil Fertility and Led to Soil Degradation in Arid and Semi-Arid Regions

Abstract: Underground coal mining in western China causes heavy land subsidence and alters the soil ecology. However, the effects of land subsidence on soil fertility are not currently known, and the key factors governing its impact remain unclear in sandy land. We investigated the effects of land subsidence induced by underground mining on the soil quality in western China. Soil samples were collected at 0–15 cm and 15–30 cm from control and subsidence areas in three coal mines. The results showed that the soil water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 44 publications
3
49
0
1
Order By: Relevance
“…Coal mining operations reduced the mean content of soil nutrients, which were consistent with previous studies [36,37], showing that land subsidence caused by coal mining could induce losses in surface soil nutrients. This might be due to the subsidence in the coal mining area resulting in the vertical leakage of soil nutrients from the top layer to the deeper layer [38].…”
Section: Discussionsupporting
confidence: 91%
“…Coal mining operations reduced the mean content of soil nutrients, which were consistent with previous studies [36,37], showing that land subsidence caused by coal mining could induce losses in surface soil nutrients. This might be due to the subsidence in the coal mining area resulting in the vertical leakage of soil nutrients from the top layer to the deeper layer [38].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the soil moisture in an area with ground fissures is commonly lower than that in an unmined area, as has been documented in previous research (Hu & Ceng, 2016; Ma, Gao, Zhang, Dong, & Huang, 2013). Furthermore, ground fissures were also found to result in the degradation of other soil properties, such as creating a loss of soil fertility, decrease in field capacity, and change in the soil microbial community (Ma, Zhang, Ruan, Guo, & Chai, 2019). These changes in hydrological conditions resulting from underground mining would limit the growth of plants and the development of the plant community in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of OTUs unique to each site was high relative to that of the core OTUs, indicating that subsidence led to a certain degree of species dissimilarity across the landscape. Many studies have shown that coal mining can decrease the abundance of soil microorganisms [ 2 , 10 , 29 ]. Artificial interference includes agriculture and coal mining, and ecological disturbances have been reported to influence soil AMF richness [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%